Ductal Carcinoma In Situ and Microinvasive/Borderline Breast Cancer - Newman, Lisa A.; Newman, Lisa A.; Bensenhaver, Jessica M.; Bensenhaver, Jessica M. (Springer New York : Imprint: Springer, 2015)
This volume reviews the evolution of information regarding the epidemiology of DCIS and its modes of detection, as well as treatment options as a function of both clinical trial data and ongoing investigational therapeutic prospects. Several of the challenging and clinically-relevant scenarios of DCIS that appear in daily practice is discussed, including the difficulties of distinguishing “true” DCIS from borderline patterns of other breast diseases and the therapeutic implications of differentiating these various diagnoses. Particular attention is paid to pathologic evaluation of DCIS, including histologic patterns and the importance of margin evaluation/margin control. The text also explores the data regarding DCIS in medical research in hereditary susceptibility for breast cancer and race/ethnicity-associated disparities in breast cancer. Written by experts in the field, Ductal Carcinoma In Situ and Microinvasive/Borderline Breast Cancer is a comprehensive, state-of-the art review of the field, and serves as a valuable resource for clinicians, surgeons and researchers with an interest in breast cancer.